PENERAPAN PENDEKATAN PEMBELAJARAN INKUIRI UNTUK MENCAPAI KETUNTASAN BELAJAR SISWA PADA POKOK BAHASAN LAJU REAKSI DI KELAS XI MIA SMAN 10 PEKANBARU - R.Okta Rise Armis Rise Armis; Johni Azmi Azmi; Betty Holiwarni Holiwarni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : Research on the application of inquiry learning approach aims to achieve student’s mastery learning on the topic of the reaction rate in class XI MIA 3 Senior Hight School Number 10 Pekanbaru. This research used one shot-study case design. Time of data retrieval from the date November 5rd – 11rd 2014. The sample was selected from the five existing classes, obtained class XI MIA 3. Data analysis technique used the percentage calculation of mastery learning classical. Based on the results of data processing obtained mastery learning classical of knowledge competency is 91,43 %, attitude competency is 100% and skill competency is 100%, means that the application of inquiry learning approach can achieve student’s mastery learning on the topic of the reaction rate in class XI MIA 3 Senior Hight School Number 10 Pekanbaru. Keywords : Inquiry Learning, Mastery Learning, Reaction Rate.